2018
DOI: 10.1021/acsnano.7b08708
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrogen in High-Yield Growth of Boron Nitride Nanotubes at Atmospheric Pressure by Induction Thermal Plasma

Abstract: We recently demonstrated scalable manufacturing of boron nitride nanotubes (BNNTs) directly from hexagonal BN (hBN) powder by using induction thermal plasma, with a high-yield rate approaching 20 g/h. The main finding was that the presence of hydrogen is crucial for the high-yield growth of BNNTs. Here we investigate the detailed role of hydrogen by numerical modeling and in situ optical emission spectroscopy (OES) and reveal that both the thermofluidic fields and chemical pathways are significantly altered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 44 publications
5
91
0
Order By: Relevance
“…Figure S3 shows FE-SEM images of the BNNTs synthesized at various pressures, which indicated that a large amount of BNNTs was synthesized at each pressure condition. As shown in Figure S3c, amorphous boron and a minimal amount of h-BN flakes were observed as impurities in our grown BNNTs through FE-SEM, which is similar to previous reports 34,37,45 . Figure S4 shows the HRTEM images of BNNTs synthesized under different pressure conditions, which corresponded to the change in BNNT color shown in Figure 2d.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure S3 shows FE-SEM images of the BNNTs synthesized at various pressures, which indicated that a large amount of BNNTs was synthesized at each pressure condition. As shown in Figure S3c, amorphous boron and a minimal amount of h-BN flakes were observed as impurities in our grown BNNTs through FE-SEM, which is similar to previous reports 34,37,45 . Figure S4 shows the HRTEM images of BNNTs synthesized under different pressure conditions, which corresponded to the change in BNNT color shown in Figure 2d.…”
Section: Resultssupporting
confidence: 90%
“…Thus, researchers in the BNNT field are interested in the selective synthesis of SWBNNTs and DWBNNTs because they have superior properties to those of MWBNNTs due to structural perfection and quantum confinement effects. However, studies on controlling the number of BNNT layers and reducing various impurities such as amorphous boron and h-BN remain in the early stages 20,34,37,40,45 .…”
mentioning
confidence: 99%
“…at NRC produced high-quality BNNTs at the rate of 20 g/h, without using a metal catalyst 35 . They also suggested a growth mechanism of BNNTs in this method involving the catalytic activity of hydrogen 37 . An extended-pressure inductively coupled plasma system that offers excellent flexibility in the use of various boron precursors, developed by Zettle’s group from UC Berkeley, can yield BNNTs at an even higher rate (35 g/h); however, the purity of the final products is slightly inferior, because a minority of other boron nitride byproducts (nanoribbon, nanococoon) are also attained 36 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in doing so, it requires a profound understanding of the growth mechanism of BNNT in every single method. Recently, computer simulation and in situ diagnostic tools to evaluate every critical factor from several research groups have initially provided some insight into growing process of BNNT [ 51 , 53 , 58 ]. On the other hand, the widespread availability of BNNT has triggered great interest in the development of BNNT applications.…”
Section: Discussionmentioning
confidence: 99%
“…With the addition of hydrogen, the B–N–H was formed and promoted the formation of BNNT by efficiently reacting with the boron nano-droplet rather than nitrogen molecules. Hydrogen effect was investigated through additional simulations and in situ optical emission spectroscopy (OES) study [ 58 ]. Zettle et al obtained double-walled BNNTs at very high production rate (35 g/h) while developing the extended pressure inductively-coupled plasma system (EPIC) method in high-pressure conditions based on induction plasma method (Fig.…”
Section: Bnnt Synthesis Methodsmentioning
confidence: 99%